Chord properties of digital straight line segments - Samieinia, Shiva (MATHEMATICA SCANDINAVICA, 2010)
We exhibit the structure of digital straight line segments in the 8-connected plane and in the Khalimsky plane by considering vertical distances and unions of two segments.